RUANG TERBUKA DAN TINGKAT KEBUGARAN JASMANI BAGIAN DARI PEMBANGUNAN OLAHRAGA KABUPATEN WONOGIRI - Desi Natalia; Sugiyanto -; Kiyatno - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Development is an effort purposed at achieving better conditions. In the sector of sports, development not only based on the medals procuration in the competition multievent, but open space for sports and also the level of physical fitness is part of the Sport Development Index (SDI). The purpose of this study to determine the level of open space for sports and the level of physical fitness society of Wonogiri. This study is evaluation sport development by using a qualitative method. Data collection technique used observation, Multistage Fitness Test (MFT) and documents. This study was conducted in the Wonogiri regency with the subject are consisted of the child (7-12 years) 30 people, adolescence (13-17 years) 30 people and adults (18-40 years) 30 people. each age group consisted of 15 men and 15 women. To get open space data by observation and the subjects do Multistage Fitness Test (MFT) to measure the level of physical fitness. Based on the result of study, it can be concluded that the open space index of 0,711including intermediate category and physical fitness index of 0.315 includinglow category if the terms of the norm Sport Development Index (SDI). Keyword: Public Participation and Physical Fitness.